Preliminary Data on the Structure and Potential of the Tocomar Geothermal Field (Puna Plateau, Argentina) - Giordano, G. (2016)
This study presents new stratigraphic, structural and hydrogeological data on the Tocomar geothermal volcanic area (Puna plateau, Central Andes, NW Argentina), together with preliminary geochemical and magnetotelluric data. The main geothermal reservoir is located within the fractured Pre-Palaeozoic-Ordovician units. The reservoir is recharged by meteoric waters. Geothermal fluids upwell where main regional structures intersect secondary structures associated with the development of the Tocomar basin. Preliminary data indicate a reservoir temperature of ∼ 200°C and a local geothermal gradient of ∼ 130°C/km associated with the Quaternary volcanic activity in the Tocomar area.